1976
DOI: 10.7326/0003-4819-85-6-724
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Metabolic State in Chronic Renal Failure

Abstract: Thirty-eight patients with chronic renal insufficiency who were in a dialysis program underwent studies of thyroid function and metabolic status. Mean values for serum total and free thyroxine (T4) concentrations and thyroxine-binding globulin capacity were within normal limits. Although mean serum total triiodothyronine (T3) concentration was normal, 43% of the group had low serum T3 and 54% had low serum free T3 concentrations. Serum thyrotrophin (TSH) concentrations were normal in all but four subjects who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 18 publications
12
65
1
Order By: Relevance
“…On the other hand, accumulation of toxic uremic solutes alters the central (hypothalamic) control of the pituitary gland, and the TSH response to thyrotropinreleasing hormone is subnormal in these patients [15]. In contrast, [16]. Central effects apart, toxic uremic solutes inhibit protein binding of thyroxin [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, accumulation of toxic uremic solutes alters the central (hypothalamic) control of the pituitary gland, and the TSH response to thyrotropinreleasing hormone is subnormal in these patients [15]. In contrast, [16]. Central effects apart, toxic uremic solutes inhibit protein binding of thyroxin [17].…”
Section: Discussionmentioning
confidence: 99%
“…TSH values did not show any linear correlation with glomerular filtration rate in our study.One similar study showed similar results which was conducted by Spector and Ramirez et al 11,21 Dudani et al 14 , Karunanidhi et al 15 . These studies depicted abnormality in hypophyseal mechanism of TSH release in uraemic patients as the TSH response to the TRH was blunted.Another study which was conducted by Joseph et al and Hardy et al 16,17 11,13 study showed linear correlation between mean serum T3 and T4 and severity of renal failure.Among 50 patients of CKD, 17 patients did not show any thyroid function abnormalities but out of them 11 had symptoms suggestive of hypothyroidism which accounts for 64.7%.Features of hypothyroidism such as delayed ankle jerk was present in 2 patients, out of which one were hypothyroid. Papilloedema was found in one patient who is a hypothyroid and goitre was found in one patient who is a hypothyroid.Previous studies by Quionverdeet a1 20 reported high preponderance of hypothyroidism in CKD.…”
Section: Low T3 Normal "A Study Of Thyroid Function Abnormalities In mentioning
confidence: 91%
“…With the introduction of radioimmunoassay and chemiluminescense assay methods for estimation of thyroid hormones, the thyroid status in CKD has been studied extensively by a host of workers. Most of the authorities have demonstrated biochemical evidence of hypothyroidism and a few have detected hyperthyroidism, even goiter and exophthalmos like Silverberg et al and carter et al 4,5 Although uremia shares some of the clinical features of myxedema, overt clinical disturbances of thyroid function ordinarily does not occur Grantham et al and Spector et al 6,7 In CKD Ramirez et al and Lim et al observed biochemical evidence of hypothyroidism but in contrast Spector et al reported clinical euthyroidism in CKD patients on HD. [7][8][9] Various workers have attributed different causes for thyroid dysfunction however Victoria et al in their study of CKD patients before HD, during HD and after renal transplant comprehended the abnormalities at three different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the authorities have demonstrated biochemical evidence of hypothyroidism and a few have detected hyperthyroidism, even goiter and exophthalmos like Silverberg et al and carter et al 4,5 Although uremia shares some of the clinical features of myxedema, overt clinical disturbances of thyroid function ordinarily does not occur Grantham et al and Spector et al 6,7 In CKD Ramirez et al and Lim et al observed biochemical evidence of hypothyroidism but in contrast Spector et al reported clinical euthyroidism in CKD patients on HD. [7][8][9] Various workers have attributed different causes for thyroid dysfunction however Victoria et al in their study of CKD patients before HD, during HD and after renal transplant comprehended the abnormalities at three different levels. 10 First there is a blunted Thyroidstimulating Hormone (TSH) response to Thyrotropinreleasing Hormone (TRH) suggesting pituitary dysfunction, second there occurs intrathyroidal defects in hormonogenesis or hormonal secretion or both and last being impaired conversion of T4 to T3 in extra thyroidal tissues, resulting in selective and marked reduction in serum TT3 concentration.…”
Section: Introductionmentioning
confidence: 99%